CAUSES OF PAPILLOMAVIRUS AND HOW TO GET RID OF THEM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Papillomas are non-cancerous, primary growths. Papillomas are often called warts and verrucas when they occur on the skin. They can also appear on the surface of moist tissues that line the inside of the body, such as the intestines or respiratory tract. The human papillomavirus is the most common cause of papillomas. Some strains of papillomavirus can also cause cancer.